Daily rumination time of lactating dairy cows under heat stress conditions. (February 2020) - Müschner-Siemens, Theresa; Hoffmann, Gundula; Ammon, Christian; Amon, Thomas
Abstract: The dairy industry in regions with moderate climates, such as Central Europe, will be increasingly challenged in the future by climate change. The problem of heat stress will especially affect dairy husbandry in naturally ventilated barns (NVB). The approach of the study was to determine a heat stress threshold of the average daily temperature-humidity index (THI) that results in changes in the daily rumination time (RT) of lactating, high-yielding cows. The data set was composed of a high sample size of 183 cows and long-duration measurements of 21240 daily observations over two years from June 2015 to May 2017, which were collected in an NVB in Groβ Kreutz, Germany. The THI was calculated in 5-min intervals by data from several sensors in different positions inside the barn. Additionally, every cow from the herd of an average of 53 cows in the experimental procedure was wearing a neck collar with a Lely Qwes HR system that provided the RT 24 h a day (12 2-h recordings were summarized). The study showed that heat stress also negatively influenced RT in moderate climates. The heat stress threshold of 52 THI was determined by broken-stick regression and indicated changes of RT of lactating dairy cows in Germany. During the experimental period, the heat stress threshold for RT was reached from April to September for up to 720 h per month. The changes in RT to the heat stress threshold will be affected by cows' characteristics. Therefore, we considered several cow-related factors, such as milk yield (MY), lactation number (LN), lactation stage (days in milk, or DIM) and pregnancy stage (P) to better understand cows' individual reactions to heat stress. Multiparous, high-yielding cows in later lactation stages are potentially more strongly affected than other cows. Highlights: Climate change affects RT of lactating dairy cows in moderate climate like Germany. A determined heat stress threshold for changes in RT is a THI of 52 in Germany. Cows' individual reactions to heat stress are influenced by cow-related factors. Multiparous, high-yielding cows in later lactation stages are more vulnerable.